AGE AND SEX STRUCTURE OF THE POPULATION AS A FACTOR OF GEODEMOGRAPHICAL DEVELOPMENT (FOR EXAMPLE POLTAVA REGION) - Барило, Ірина (Human Geography Journal, 2014)
The article analyzes the main features of formation of age and sex structure of the population as qualitative characteristics geodemodraphical processes in Poltava region. Calculated main geodemographical components (fertility, mortality, natural increase). The features of the distribution of urban and rural population by sex and age. Defined demographic load (maximum and minimum values) for the districts and towns of the region. Considered territorial characteristics of gender and age structure of the Poltava region.